2018
DOI: 10.1002/jso.25156
|View full text |Cite
|
Sign up to set email alerts
|

Lower expression of tumor microRNA‐26a is associated with higher recurrence in patients with hepatocellular carcinoma undergoing surgical treatment

Abstract: Reduced miR-26a expression is a common phenomenon in HCC arising in North American patients with different underlying liver diseases and may increase recurrence and mortality after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…HBV might influence miR expression and induce inflammatory cytokine production [91]. Previous reports indicated that some hepatic miRs are involved in the pathogenesis of HBV-associated HCC [92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142], with certain serum miRs involved in HBV-associated HCC also potentially useful as biomarkers (Table 2).…”
Section: Molecular Mechanisms Of Hbv-associated Hccmentioning
confidence: 99%
“…HBV might influence miR expression and induce inflammatory cytokine production [91]. Previous reports indicated that some hepatic miRs are involved in the pathogenesis of HBV-associated HCC [92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142], with certain serum miRs involved in HBV-associated HCC also potentially useful as biomarkers (Table 2).…”
Section: Molecular Mechanisms Of Hbv-associated Hccmentioning
confidence: 99%
“…Furthermore, low expression of miR-26a correlated with a poor prognosis of HCC patients [144,176]. This finding was also confirmed in patients with HBV-induced HCC [177]. MiR-26a was also associated with resistance to the chemotherapeutic drug doxorubicin [173].…”
Section: Microrna-26amentioning
confidence: 58%
“…Tumour progression was evaluated in three studies [16,18,19] . Recurrence rate and prognosis were the main objectives in four studies [17,[20][21][22] , respectively eight studies [23][24][25][26][27][28][29][30] . Lee et al studied the correlation between AFP values and the resection margins in patients with minor or major liver resections for HCC [31] .…”
Section: Resultsmentioning
confidence: 99%
“…The RNAs were used as prognostic markers for recurrence rate and mortality, overall survival and tumor progression. Jones et al and von Felden et al investigated the role of miRNAs regarding the recurrence of hepatocellular carcinoma after curative liver resections [20,21] . Jones et al included only a North American cohort with different underlying liver conditions demonstrating an association between lower tumoral miRNA-26a expression and the postoperative recurrence rate [21] .…”
Section: Rna Studiesmentioning
confidence: 99%
See 1 more Smart Citation